2012
DOI: 10.1111/j.1574-695x.2012.01025.x
|View full text |Cite
|
Sign up to set email alerts
|

Mycobacterium tuberculosisH37Rv is more effective compared to vaccine strains in modulating neutrophil functions: anin vitrostudy

Abstract: Neutrophils are the primary cells contributing to initial defense against mycobacteria. Yet, little is known about the potential of various mycobacterial strains to stimulate neutrophils. This study was focused to compare the differential capacity of vaccine strains, Mycobacterium bovis bacillus Calmette-Guerin (BCG) and Mycobacterium indicus pranii (Mw), and laboratory strain H37Rv to activate and enhance neutrophil functions. The expression of phenotypic markers like Fcγ receptor, toll-like receptor (TLR), a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
3
7
0
Order By: Relevance
“…These results confirmed that the expression of TLR4 on CD14+ monocytes, but not TLR2, is upregulated in individuals who received BCG vaccines compared with the findings in unvaccinated individuals [58]. In the case of neutrophils, Mtb stimulation also induces the expression of TLR4, TNFα, and scavenger receptors [59,60]. Another study demonstrated that TLR4 expression is required to protect mice against chronic Mtb infection.…”
Section: Tlr4supporting
confidence: 59%
“…These results confirmed that the expression of TLR4 on CD14+ monocytes, but not TLR2, is upregulated in individuals who received BCG vaccines compared with the findings in unvaccinated individuals [58]. In the case of neutrophils, Mtb stimulation also induces the expression of TLR4, TNFα, and scavenger receptors [59,60]. Another study demonstrated that TLR4 expression is required to protect mice against chronic Mtb infection.…”
Section: Tlr4supporting
confidence: 59%
“…The role of NETs in TB is still controversial, however a correlation between plasma NET levels in patients with TB and disease severity has been observed (80). Moreover, many suggest that NETs have a role in minimizing the spread of an infection (196). We were in this project able figure 1).…”
Section: Resultsmentioning
confidence: 91%
“…Additionally, the reduction of CD64 was directly correlated with TLR2 and TLR4. In this regard, a directly proportional expression between CD64, TLR2, and TLR4 has been described in monocytes differentiated into macrophages from peripheral blood [ 71 ] and neutrophils from tuberculosis patients [ 72 ], but not in vitro macrophages differentiated to a pro-inflammatory profile. These antecedents suggest that there might be a functional relationship between the two, which would help explain the reduction in TLRs observed on the surface of LPS-stimulated macrophages in our experimental model.…”
Section: Discussionmentioning
confidence: 99%